Non endoscopic predictor of esophageal varices in patients with cirrhosis of liver from tertiary care hospital (Panacea Journal of Medical Sciences, 2022)
Background: With the rising mortality rate, worldwide liver cirrhosis has been ranked as the 13th leading cause of mortality. Portal hypertension is one of the common consequences of liver cirrhosis. Further, portal hypertension has its own complications and the most serious among them is the risk of development of esophageal varices (EV) caused by increased hepatic vascular resistance related to hepatic fibrosis and regenerative nodules.Aim: To identify the non-endoscopic predictor of esophageal varices in patients with liver cirrhosis in a tertiary care hospitalMaterials and Methods: A prospective study was carried out at the tertiary care hospital of Dr. PDMMC, Amravati between the period September 2018 to March 2020. One hundred patients diagnosed with liver cirrhosis were taken for the study. The patients were selected based on the clinical, the radiological and historical data.Results: The patients were divided into two groups, namely the small size of varices group where n=71 and large size of varices group where n=29. Factors such as platelet count, serum albumin, spleen (cm), PV (mm), platelet count and child-pugh classification were considered important as their p values were less than 0.05.Conclusion: The platelet count and the spleen size showed the difference among the patients belonging to small varices and larger varices group, respectively. Ascites was noted in 90% of the cases. 65% of the patients suffered from portal gastropathy and esophageal varices.